Kedah 100 tahun, 1900-2000 isu-isu politik & sosioekonomi (Sintok Penerbit Universiti Utara Malaysia, 2002)
Historical, political, and socioeconomic development of Kedah from 1900 to 2000.
Includes bibliographical references.